Pollicipes pollicipes as a Biomonitor of PAHs Contamination in Seawaters of the Northwest Coast of Portugal - Reis P.A. (2017)
Simple, fast, and economic solid phase microextration–gas chromatography–mass spectrometry (SPME–GC–MS) methods were validated for the determination of 8 United States Environmental Protection Agency priority polycyclic aromatic hydrocarbons (PAHs: naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene, fluoranthene and pyrene) in coastal seawaters and soft tissues of goose barnacles Pollicipes pollicipes. Under the optimized conditions, the limits of detection ranged from 0.012 to 1.069 ng L−1 and 0.002 to 0.061 µg kg−1 (dry weight basis) for seawaters and soft tissues, respectively. Precision varied between 3.9% and 20.0% for seawaters and between 8.4% and 19.1% for soft tissues, which are acceptable repeatabilities for environmental analyses. Finally, the accuracy of the optimized conditions also showed suitable recoveries, varying between 81.5% and 105.5% in spiked seawater samples and between 88.0% and 103.4% in the standard reference material for organics in mussel tissues (NIST SRM 2977). These methods were applied to a monitoring program performed along the northwest coast of Portugal during four seasons in 2011 in order to assess the levels of these compounds present in coastal waters and in the tissues of goose barnacles, one food resource of high commercial value. The results showed that although the concentrations of PAHs in seawaters and P. pollicipes varied significantly along the coast and between seasons (p < 0.05), in general the concentrations in seawater can be classified as “Class II – Good/Natural Background Concentrations” during the four seasons of 2011. As for the concentrations of PAHs in P. pollicipes, they were positively correlated (p < 0.05) with their concentrations in seawater, indicating that P. pollicipes may be an adequate biomonitor species of PAHs availabilities along the coast of Portugal throughout the year. © 2017 Taylor & Francis Group, LLC